Intrapulmonary cavitating solitary fibrous tumor: A rare case report - Dyan Wahyu Kusumaningrum; Fierly Hayati (Radiology Case Reports)
Solitary fibrous tumor (SFT) is a rare mesenchymal tumor that affects most commonly in the sixth or seventh decade of life. They account for less than 2% of all soft tissue tumors. In the thoracic region, it primarily appears in the pleura and rarely in the intrapulmonary. SFT typically presents as well-defined, oval or round, hyperdense masses. We report male 66-year-old complaint of cough, intermittent shortness of breath, and a lump in the lower right chest which has gradually increased in size. From chest MSCT results, there were cavitating lesions with solid and cystic components. FNAB and core biopsy examinations were performed. To establish a definitive diagnosis, an open biopsy followed by immunohistochemical analysis was conducted, confirming the presence of a solitary fibrous tumor (SFT).